2012
DOI: 10.1371/journal.pone.0032719
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Very Low and Very High Voice Pitch in Humans

Abstract: Manipulations of voice pitch have been shown to alter attractiveness ratings, but whether preferences extend to very low or very high voice pitch is unknown. Here, we manipulated voice pitch in averaged men's and women's voices by 2 Hz intervals to create a range of male and female voices speaking monopthong vowel sounds and spanning a range of frequencies from normal to very low and very high pitch. With these voices, we used the method of constant stimuli to measure preferences for voice. Nineteen university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 68 publications
8
65
1
1
Order By: Relevance
“…Yet our study demonstrates that pitch correspondences, typically studied with tones and music, generalize to human voice pitch. Moreover, whereas previous studies using tonal stimuli have used broad pitch ranges spanning 200-8000 Hz (see, e.g., Cabrera et al, 2005;Carnevale & Harris, 2016;Mudd, 1963;Parise et al, 2014;Pratt, 1930), we have demonstrated that frequency-elevation mapping is elicited with voice pitch manipulations of only 20-40 Hz at pitch centers of 100-250 Hz (although this degree of manipulation is still an order of magnitude larger than the just-noticeable differences for pitch detection in similar vocal stimuli; see Re et al, 2012). In addition, our results show that the influence of pitch on spatial perception goes beyond localizing sounds in space, but also affects performance in an indirect spatial task, and one that has ecological relevance.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Yet our study demonstrates that pitch correspondences, typically studied with tones and music, generalize to human voice pitch. Moreover, whereas previous studies using tonal stimuli have used broad pitch ranges spanning 200-8000 Hz (see, e.g., Cabrera et al, 2005;Carnevale & Harris, 2016;Mudd, 1963;Parise et al, 2014;Pratt, 1930), we have demonstrated that frequency-elevation mapping is elicited with voice pitch manipulations of only 20-40 Hz at pitch centers of 100-250 Hz (although this degree of manipulation is still an order of magnitude larger than the just-noticeable differences for pitch detection in similar vocal stimuli; see Re et al, 2012). In addition, our results show that the influence of pitch on spatial perception goes beyond localizing sounds in space, but also affects performance in an indirect spatial task, and one that has ecological relevance.…”
Section: Resultscontrasting
confidence: 70%
“…The PSOLA method alters one voice feature (e.g., voice pitch) while leaving other features unaltered (Moulines & Charpentier, 1990). Our pitch manipulation corresponded to approximately two times the just-noticeable difference in voice pitch perception from a series of vowel sounds (Pisanski & Rendall, 2011;Re, O'Connor, Bennett, & Feinberg, 2012), as well as body size perception from voice pitch (Smith & Patterson, 2005). Pitchmanipulated men's voices (M ± SD, raised-pitch: 122 ± 4 Hz; lowered-pitch: 99 ± 3 Hz) and women's voices (raised-pitch: 238 ± 1 Hz; lowered-pitch: 194 ± 1 Hz) spanned the natural ranges in voice pitch for each sex (Titze, 1989).…”
Section: Auditory Stimulimentioning
confidence: 99%
“…This seems unlikely to be caused by the stimuli having youthfully high voice pitches because previous research has shown that men prefer higher-pitched women"s voices even when those voices have been manipulated up to 280 or 300 Hz (Borkowska & Pawlowski, 2011;Feinberg, DeBruine, Jones & Perrett, 2008;Re, O'Connor, Bennett & Feinberg, 2012); the individual means of the manipulated higher-pitch female voices in the present study ranged from 188 to 260 Hz (see Stimuli), and so we might expect them to have provoked standard attractiveness judgments. Yet boys" and girls" voices tend to lower in pitch during the teenage years (Lee, Potamianos & Narayanan, 1999), and women perceive lower-pitched male voices to be older (e.g.…”
Section: [Tables 3 and 4 About Here]mentioning
confidence: 55%
“…Whereas the PSOLA method alters voice pitch, other aspects of the voice are perceptually unaffected (Feinberg et al, 2005). The manipulation performed here is roughly equivalent to a 20% change in Hz for women"s speech and a 13% change in Hz for men"s speech in this particular sample, which are above established JND"s for detection, attractiveness, and masculinity perception (Re et al, 2012), and takes into account the fact that pitch perception is on a log-linear scale in comparison to the natural frequencies (i.e. Hertz, Traunmüller, 1990).…”
Section: Accepted M Manuscriptmentioning
confidence: 90%